From Cyberbullying to Cybertolerance: Religious Moderation and Student Character Building - Nurhayati, Lilis (Balai Diklat Keagamaan Bandung, 2024)
Religious moderation is an essential character education strategy that emphasizes tolerance and respect for diversity. In the internet age, cyberbullying is a severe concern that threatens moderate ideals. With the increased use of social media, adolescents are frequently exposed to online bullying, which fosters an intolerant climate. This has the potential to hinder constructive character development among students. This study investigates the link between religious moderation and tolerance in a digital setting, offering fresh insights into how religious principles might be used to combat online bullying behavior. The goal of this research is to look at how religious moderation might help students build their character while also promoting internet tolerance. This study used a descriptive qualitative strategy, with interviews and observations serving as the primary data-gathering methods. From the findings, it can be inferred that students who participate in religious moderation programs are more tolerant, capable of countering bullying behavior, and more accepting of diversity. Religious moderation-based education in the digital age is critical not just for preventing cyberbullying, but also for raising a more accepting and character-driven generation.Keywords: Religious moderation; student character; cyberbullying; cybertolerance; education